Parental monitoring and support, social capital, and adolescent substance use - Karítas Rún Grétudóttir 1999- (2023)
Substance use is one of the main reasons for morbidity and mortality among adolescents. The prevalence of adolescent substance use is concerning. Therefore, it is important to identify what factors may have protective effects on adolescent substance use. There are many protective- and risk factors for adolescent substance use that can be used to produce effective prevention. Among those protective- and risk factors are parental factors which can have major influence. Exciting literature suggests that parental- monitoring and support, and parental social capital act as protecting factors for adolescence substance use. The aim of the study is to examine if parental monitoring, parental support, and social capital are related to adolescent substance use. This was a quantitative cross-sectional study with a population-based sample. The sample consisted of 2000 participants aged 15-20 years. All participants were upper secondary school students in Iceland. The result suggested that adolescent substance use is negatively related to parental monitoring, parental support, and social capital. Keywords: Adolescent, parental monitoring, parental support, social capital, substance use. Vímuefnanotkun er ein megin ástæða sjúkdóma- og dánartíðni unglinga. Algengi vímuefnanotkunar meðal unglinga er áhyggjuefni og því er mikilvægt að greina hvaða þættir það eru sem að hafa verndandi áhrif fyrir vímuefnaneyslu unglinga og hvaða þættir það eru sem að geta komið í veg fyrir eða seinkað notkun. Það eru margir verndandi og áhættuþættir fyrir vímuefnanotkun unglinga sem hægt er að nýta til að byggja upp skilvirkar forvarnir. Á meðal verndandi- og áhættuþátta er foreldraþáttur sem að getur haft gríðarlega mikil áhrif. Fyrirliggjandi þekking bendir til þess að eftirlit og stuðningur foreldra og félagsleg auðlegð séu verndandi þættir fyrir vímuefnanotkun unglinga. Markmið þessarar rannsóknar er að kanna hvort að samband sé á milli stuðnings frá foreldrum, eftirliti frá foreldrum, félagslegrar auðlegðar og vímuefnanotkun unglinga. ...